IMPROVEMENT OF E-PROCUREMENT SYSTEM USING LEAN SIX SIGMA APPROACH (CASE STUDY IN PT ANGKASA PURA II (PERSERO)) (The Indonesian Journal of Business Administration, 2019)
The General Meeting of Shareholder has set investment program for development in key performance indicators, such as infrastructure building terminal, runway, or other supporting to operate the airport as production tools that generates revenue. It processed through the procurement, with comply to the company rule that refer to guidelines of state-owned enterprises, so that, the faster procurement process and work process completed, the potential revenue recorded. The problem is, absorption of investment program in recent years has not achieve the target. The delay in the procurement process and duration of the completed, start from the tender request until the appointment issued is the topic of author's analysis.The lean six sigma synergy is the concept of operational management. The procurement process is expected to achieve lean "speed", and "six sigma" quality. The analysis is identifying potential waste using lean principles, things that cause ineffective process, and the DMAIC concept in determining problems, measuring abilities and goals, analyzing data to understand problems, improving processes and reducing the causes of problems, and implementing controls.Improvement has been made in each process, from 65 working days, to 25 working days. The speed and quality of the procurement process will facilitate the achievement of investment absorption targets.Keywords:  investment, lean, procurement, production tools, revenue, six sigma.